Generative design : visualize, program, and create with processing - Bohnacker, Hartmut, 1972-; Bohnacker, Hartmut, 1972-; Frohling, Marie, ....-; Gross, Benedikt, 1980-; Laub, Julia, 1980-; Lazzeroni, Claudius, ....- (New York : Princeton Architectural Press, 2012)
Generative design is a revolutionary new method of creating artwork, models, and animations from sets of rules, or algorithms. By using accessible programming languages such as Processing, artists and designers are producing extravagant, crystalline structures that can form the basis of anything from patterned textiles and typography to lighting, scientific diagrams, sculptures, films, and even fantastical buildings. Opening with a gallery of thirty-five illustrated case studies, Generative Design takes users through specific, practical instructions on how to create their own visual experiments by combining simple-to-use programming codes with basic design principles. A detailed handbook of advanced strategies provides visual artists with all the tools to achieve proficiency. Both a how-to manual and a showcase for recent work in this exciting new field, Generative Design is the definitive study and reference book that designers have been waiting for.
Formerly CIP.
Translated from the German.
Includes bibliographical references and index.
Keywords: 72.012 -- Architectuur. Bouwkunst; Computer art; Computer drawing; Generative programming (Computer science).; Graphic arts -- Data processing